The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico - Hendrickx, Michel E.; Ayón-Parente, Manuel (Zootaxa, 2017)
Four species of Spirontocaris are known from a few records along the coast of the Baja California Peninsula, Mexico: S. prionoata (Todos Santos Bay), S. sica (between San Benito and Cedros Islands), S. snyderi (Cedros Island), and S. truncata (off San Carlos Point). During exploratory surveys off the west coast of the Baja California Peninsula, Mexico, two specimens of Spirontocaris holmesi Holthuis, 1947, and 143 of S. sica Rathbun, 1902 (10 males, 128 females, 2 ovigerous females, and 3 damaged specimens) were collected in benthic trawl and sledge. Both species are illustrated and described. The material of S. holmesi was collected in a single locality, at 220 m depth (known depth range is 150–300 m) and is the first record for western Mexico, while the material of S. sica was collected in five localities, from 710–1102 m depth (known range, 88–849 m), increasing significantly the number of specimens known for this species. Environmental data indicate that S. sica lives below the Oxygen Minimum Zone, in poorly oxygenated water (0.22 to 0.40 ml O2/l), in a temperature range of 4.38 to 5.81 °C. Sediments associated with this species are dominated by silt (>72% in 4 out of 5 localities), with organic carbon content of 18 to 52 mgCorg/g.